Differences in gut microbes in captive pangolins and the effects of captive breeding - Jiao, Wenjing; Liu, Lina; Zeng, Zhiliao; Li, Linmiao; Chen, Jinping (Frontiers in Microbiology, 2022)
Intestinal microorganisms are crucial for health and have a significant impact on biological processes, such as metabolism, immunity, and neural regulation. Although pangolin are protected animals in China and listed as critically endangered (CR) level by The International Union for Conservation of Nature (IUCN), the population of wild pangolins has decreased sharply in recent decades. Captive breeding has been adopted to protect pangolins, but the survival is low due to gastrointestinal infections, diarrhea, and parasitic infections. Studies on intestinal microbes in pangolins may reveal the relationship between intestinal microorganisms and health and assist protection. To explore the relationship between intestinal microorganisms and pangolin health, blood parameters and intestinal microorganisms of 10 pangolins (two Manis pentadactyla and eight Manis javanica) were studied at the Shenzhen Wildlife Rescue Center. There is difference among adult Sunda pangolins (M. javanica), adult Chinese pangolins (M. pentadactyla) and sub-adult Sunda pangolins (M. javanica) in intestinal microbial composition, diversity and phenotypic diversity, which suggested that adult Sunda pangolins occupied more diversity and proportion of microbial species to resist environmental pressure than the others. Due to the captive breeding serum cortisol of pangolins was increased, and the intestinal microbial structure changed, which may affect immunity. This study provides a scientific basis for the rescue of pangolins through artificial breeding.